Comparison of the effects of buparvaquone and paromomycin on oocyst excretion and clinical parameters in diarrheal calves naturally infected with cryptosporidiosis - Evci, FZ; Şentürk, S (Journal of the Hellenic Veterinary Medical Society, 2023)
Cryptosporidium is an obligate intracellular parasite that infects a wide variety of hosts. Twenty calves with cryptosporidiosis were divided into two groups. A single dose of 2.5 mg/kg buparvaquone was administered intramuscularly to one group, while 100 mg/kg/day paromomycin was administered orally to the other group. The results obtained from the study in which oocyst shedding and clinical parameters of sucking reflex, mental status, oocyst scattering were observed in both groups offer an effective control option with this study, which provides results that support the application of a single dose of buparvaquone injection against the complex treatment methods applied to calves with cryptosporidiosis in the field. In this study, a significant decrease in oocyst shedding and rapid improvement in clinical findings were observed in calves.